2022
DOI: 10.3390/ijerph19052811
|View full text |Cite
|
Sign up to set email alerts
|

How Comorbidities Affect Hospitalization from Influenza in the Pediatric Population

Abstract: Influenza is a contagious respiratory illness and can lead to hospitalization and even death. Understanding how comorbidities affect the severity of influenza can help clinical management. The aim of this study is to offer more information about comorbidities that might be associated with the severity of influenza in children. We used a statewide network in Rhode Island, USA, to extract data for laboratory-confirmed influenza cases among children 19 years old or younger. We identified 1169 lab-confirmed influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…The findings of our study on hospitalization outcomes of young children hospitalized with influenza showed higher frequency of ICU admission than observed for both historical seasonal influenza (2004–2009) and the H1N1 pandemic strain, but similar length of ICU stay ( 23 25 ). Our reported hospitalization LOS among the influenza cohort is similar to that previously reported among children hospitalized with influenza ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…The findings of our study on hospitalization outcomes of young children hospitalized with influenza showed higher frequency of ICU admission than observed for both historical seasonal influenza (2004–2009) and the H1N1 pandemic strain, but similar length of ICU stay ( 23 25 ). Our reported hospitalization LOS among the influenza cohort is similar to that previously reported among children hospitalized with influenza ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…A significant proportion of patients seeking health care are prone to severe illness from influenza due to comorbidities. Secondary bacterial pneumonia is a common complication associated with age and immunocompromised status, along with pre-existing medical conditions [ 10 , 11 , 12 , 13 ]. HCWs comprise an occupational group with increased exposure to the virus, and therefore have an increased chance of illness and transmission [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%